PEMODELAN PRODUK DOMESTIK REGIONAL BRUTO PROVINSI JAWA TENGAH DENGAN PENDEKATAN SPATIAL AUTOREGRESSIVE CONFUSED (SAC) - Haznam Prabowo; Abdul Karim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Economic growth becomes one indicator of the state's economic condition.Increased economy is done by increasing development in various economicsectors and equitable economic development to the regions. Therefore, with theequalization of economic development will provide an increase in the value ofgross domestic product of a region. In this research, the description of grossregional domestic product and influencing factors from the territorial point ofview with costumaize weighting matrix, and spatial autoregressive confusedPDRB modeling using spatial effect on response and residual variables. Theresults showed that the spread of GRDP in Central Java Province has a patternthat clustered between adjacent areas. Based on the GRDP relationship withthe variables that affect the workforce (TK), human capital (HC), roadinfrastructure (INF), it can be interpreted that the similarities and differences incharacteristics of each district that close together cause increase or decreaseGDP Central Java Province. This study was conducted with the aim ofdetermining the weighting matrix and modeling the Central Java GRDP withthe appropriate weighting matrix. Based on SAC model analysis results aresignificantly better than OLS model with AIC value. The significant variablesdirectly affect human capital. While the indirect effect occurs on residuals.Keywords: GRDP, Spatial autoregressive confused (SAC), Spatial Econometrik